Benchmarking Kinerja Sistem Operasi Linux dan Windows dalam Pengelolaan Proses dan Memori - Dwi Asa Verano; Evi Purnamasari (Universitas PGRI Kanjuruhan Malang, 2025)
The operating system plays an important role in managing computer resources, especially in the aspect of process and memory management. Currently, many do not know the level of operating system performance between Linux and Windows in managing processes and memory. This study aims to analyze and compare the performance of Linux and Windows operating systems in the context of multitasking process management and the efficiency of physical and virtual memory usage. The method used is a comparative experiment with direct testing using identical hardware and specifications. The parameters tested include CPU efficiency, context switching speed, idle memory usage, swap activation, and system response time when given a high load. The results of the study show that Linux has advantages in process load distribution, memory efficiency, and system stability when handling heavy loads. Windows, on the other hand, excels in application compatibility and ease of system monitoring through a graphical interface. Both systems have different characteristics that are suitable for different usage contexts. Recommendations are given based on the findings that Linux is more optimal for server environments and heavy computing, while Windows is more suitable for general desktop users with high graphics needs, with this the user can choose which operating system suits their needs.